Trademark Registration Law as an Effort to face the Growth of the Digital Economy - Kurniati, Grasia (Universitas Islam Lamongan, 2023)
The progress of today's digital economy can be put to the best use for the creation of a work that produces the greatest economic benefits for the creator. The new work created by one's creativity must be legally protected through Copyright protection. The research method used in this study is normative juridical legal research, namely legal materials, besides that primary legal materials are also used as support for secondary legal materials and for the analysis of legal materials carried out with qualitative juridical analysis methods. The results of the research and discussion reached several conclusions, namely First, the legal concept of Brands has been known since the Dutch East Indies era, first known as a brand in Law Number 21 of 1961 concerning Trademarks and Business Marks, then experienced various dynamics until finally the current trademark regulation is Law Number 20 of 2016 concerning Brands and Geographical Indications. Secondly, Indonesia adheres to a Trademark registration system with a constitutive system, registration is a must in order to obtain Trademark rights, in the absence of state registration will not give rights to the Mark to the owner of the Mark and the First-to-file system means that the registration of a mark will only be given to the party who first submits a registration request for a mark. Third, a mark will only receive legal protection if it has been registered with the Directorate of Trademarks. In Indonesia, in carrying out and providing legal protection there are two means of legal protection, namely Preventive and Rerpressive Legal Protection Facilities.